Digital marketing strategies to improve business performance of Malaysia SMEs - Azizan, Azit; Wan Khairul Anuar, Wan Abd Manan; Mazita, Mokhtar; Nisa Farzana, .; Chee, Wei Ming (Academia Industry Network, 2021)
Changes in patron behavior require firms to reconsider their advertising and marketing techniques in the digital domain. Currently, a massive part of the associated studies is targeted extra on how the SMEs control their advertising and marketing strategies. Are they advertising and marketing strategies nonetheless observe the traditional vintage way? Or they already moved on and pass together with the current generation? To redress this shortcoming, this examination adopts the perspective of the firm to facilitate a knowledge of virtual advertising and marketing and social media utilization as well as its blessings and inhibitors. Based on a survey of SMEs, this newsletter shows that they face internal and outside pressures to adopt a digital presence in social media systems. In this paper, we hypothesize 4 virtual marketing techniques (social media, site engine optimization, content material marketing, and electronic mail advertising) as determinants of competitive advantage for SMEs’ enterprise overall performance. Based on a pattern of 129 Malaysian SMEs and the use of partial least squares (PLS) structural equation modelling, the outcomes found out that 3 of the cited techniques cause aggressive gain. The aim of this newsletter is supposed to perceive the element of digital marketing for commercial enterprise overall performance of SME and to investigate the most effective element in virtual advertising and marketing utilized by SME. Particularly, there is an insufficiency of empirical verification of the usage of e-marketing by means of SMEs (Humaira, Hamid , & Asghar, 2017). SMEs also need to introduce their products to overseas market, however they regularly lack resources, skills, and marketplace strength because they enjoyed the usage of the conventional multinational agencies to introduce their products into foreign markets and that they regularly rely upon out of doors resources for each new entrants and further development in their innovation behaviour. Result suggests that Malaysian SME use and practice the digital marketing techniques to improve the business overall performance. They moved in conjunction with the contemporary era and left the traditional and vintage methods. By the usage of virtual advertising techniques, they can improve their commercial enterprise overall performance. Conclusions are drawn; the limitations and instructions for similarly investigations of the construct are provided.